The Effect of Aloe Vera Solution on Chemotherapy-Induced Stomatitis in Clients with Lymphoma and Leukemia: A Randomized Controlled Clinical Trial - Parisa Mansouri; Maryam Haghighi; Noushin Beheshtipour; Mani Ramzi (Shiraz University of Medical Sciences, 2016)
Background: Stomatitis is the most common complication of chemotherapy. This study aimed to assess the effect of aloe vera solution on stomatitis and its pain intensity in patients undergoing chemotherapeutic procedures. Methods: In this randomized controlled clinical trial, 64 patients with Acute Myeloid Leukemia and Acute Lymphocytic Leukemia undergoing chemotherapy were randomly divided into a control and an intervention group. The intervention group patients were asked to wash their mouths with 5 ml of aloe vera solution for two minutes three times a day for 14 days. The control group patients, however, used only the ordinary mouthwashes recommended in hematologic centers. The patients' mouths were examined by two assistants on days 1, 3, 5, 7, and 14. The intensity of stomatitis was recorded according to WHO stomatitis intensity checklists and pain was evaluated using Visual Analog Scale. The data were analyzed by SPSS statistical software, version 18. Results: The results showed that aloe vera solution mouthwash significantly reduced the intensity of stomatitis and its pain in the intervention group compared to the control group. On the first day, no significant difference was found between the two groups regarding the mean intensity of stomatitis (P=0.178) and pain (P=0.154). However, a significant difference was observed between the two groups in this regard on other days (days 3-14: P=0.001 for stomatitis intensity, P=0.001 for pain). Conclusions: Aloe vera solution can improve the patients' nutritional status, reduce stomatitis and its pain intensity, and increase the patients' satisfaction.